Pengaruh Penambahan Natural Rubber Pada Ban Dalam Dengan Metode Presure - Akhmad Herdianto; Zaid Sulaiman; Dodi Iwan Sumarno (Jurnal Permadi : Perancangan, Manufaktur, Material dan Energi, 2023)
The inner tube determines the effectiveness and efficiency of a commercial transportation vehicle, where the inner tube is expected to have high durability against friction with the outer tire and to have high tensile stress when holding a heavy load. To answer this condition, the process of adding natural rubber material to the inner tube was carried out using the pressure method with 2 variables, namely one layer of inner tube and one layer of natural rubber which was affixed to the outer side of the inner tube, as well as one inner tube with two layers of natural rubber located on the side outside and inside on the inner tube. Then the testing process is carried out, namely tensile brake and hardness to obtain data to determine the effect of adding natural rubber to the inner tube using the pressure method as one of the references for producing better inner tubes. After the research process was carried out, the results of the tensile brake test were 20.4 Kgf on the first specimen, 23.8 Kgf on the second specimen, 31.05 on the third specimen. Furthermore, from the hardness test, a result was obtained, namely 52° on the first specimen, 48° on the second specimen, 44° on the third specimen.